Jungle doctor on the hop eaudiobook - White, Paul (Jungle Doctor Stories., 2012)
The Witchdoctor's magic appears to be working. A dozen people have already died and many more are falling prey to this mysterious illness that is plaguing the village.What is this killer disease that is more powerful than an angry elephant, more terrifying than a mighty leopard, more deadly than a roaring lion?Wil the Jungle doctor be able to fit together the pieces of the puzzle in time?Another thrilling adventure from Paul White based in Mvumi hospital, Tanzania.